Dental caries and treatment needs in relation to nutritional status among children with congenital heart disease - Al-Haidary, Marwa J; Radhi, Nada J (Journal of Baghdad College of Dentistry, 2017)
Background: Congenital heart disease is one of the most common developmental anomalies in children. These patients commonly have poor oral health that increase caries risk. Dental management of children with congenital heart disease requires special attention, because of their heightened susceptibility to infectious endocarditis. The aims of this study were to assess the severity of dental caries of primary and permanent teeth and treatment needs in relation to nutritional indicator (Body Mass Index) among children with congenital heart disease. Materials and Methods: In this case-control study, case group consisted of 399 patients aged between 6-12 years old with congenital heart disease were examined for dental status in Ibn Al-Bitar specialized center for cardiac surgery in Baghdad/Iraq. A case-matched group (healthy control) of 485 children was also examined from primary schools in Baghdad city. Diagnosis and recording of dental caries and treatment needs were recorded according to the criteria of WHO (1997). The assessment of nutritional status (BMI) was performed following Centers for Disease Control and Prevention growth chart (2000). All data were analyzed using IBMSPSS version 23. Results: Results recorded the highest mean rank value of (DMFS)and (dmfs) were among CHD cases than control group with statistically high significant difference. Results revealed the mean rank values of (ds, ms, fs and dmfs) were higher at age group 6-7 years among CHD cases, while the mean rank values of (DS, MS, FS and DMFS) were higher at age group 12 years with statistically high significant difference among age group. The mean rank values of all types of treatment needs were recorded to be higher among CHD cases than control group, except for children no treatment needs, these differences were statistically highly significant. Also this study found that the mean rank values of caries experience (ds, ms, fs and dmfs) were higher among wasted than well nourished CHD cases with statistically highly significant for dmfs. Moreover, the mean rank values of all types of treatment need required were higher among wasted CHD cases than well nourished; however, the differences were statistical highly significant. Conclusion: The study revealed that these children are â€œat riskâ€ from dental disease and malnourished, the primary focus should be on oral hygiene instructions, the awareness of infective endocarditis and they required a development of preventive programs.